Information cards and a design to extend the claim model to incorporate geolocation - Evans, Matthew (Department of Computer Science, 2023)
The rapid adoption of the internet has occurred despite the lack of a ubiquitous identity meta-system. The status quo is a patchwork of proprietary security systems. A number of security issues have arisen as a result which threaten to lead to a loss of trust in the internet, and may limit the scope of applications built on it; effectively constraining the potential of the internet as a platform for business and services. Current initiatives by a broad consortium of industry leaders promise a vastly improved landscape with a set of interoperable protocols and systems, built on open specifications, and guided by a set of core identity principles, enabling a more secure online experience. Simultaneously there have arisen a large number of location aware web application and services which detect and use a user's location to enhance their application experience. These advances, although useful, present new security and privacy issues. This paper investigates the operation of one of the new identity technologies, information cards, and proposes extensions to the existing supported schemas to incorporate recent advances in geo-location technology. The proposal is supported by reference to existing open source implementations.